PROBLEMS IN THE APPLICATION OF PRINCIPLES OF EVIDENCE-BASED MEDICINE TO THE MEDICAL REHABILITATION OF RHEUMATIC DISEASES - M. L. Sukhareva; T. V. Dubinina; Sh. F. Erdes; L. G. Agasarov (Научно-практическая ревматология, 2015)
The paper analyzes the main problems associated with randomized controlled studies in medical rehabilitation: patient selection; use of simulation devices as placebo; standardization of methods; blinding procedure. It presents methodological considerations for improving the quality of studies.